'Hot interpretation' of battle. (19th July 2016) - James, N.
Abstract : Tilted for us to see them straight on, 45 human skeletons were stacked in tight rows, with two more, arms out-stretched, on top of them (Figure 1 ). Below lay artillery and musket shot set out with equal neatness. Owing, perhaps, to such clinical arrangement, or to the unfamiliar angle, or perhaps to the sturdy frame marked 'lützen, 6. november 1632', or else to the gallery's classical formality, the full horror only registered later, after seeing many more bones, much finely crafted weaponry and armour, and pictures and plans of fights both modern and ancient. It was the first display in Krieg: eine archäologische Spurensuche ('War: an archaeological search for traces'), an exhibition at the Prehistory Museum in Halle shown from November 2015 to May 2016.